ROLE OF PHYSIOLOGICAL PRECURSOR AND RHIZOBIUM-WHEAT ASSOCIATIONS IN FIELD CONDITIONS - M. A. Qureshi1; F. Mujeeb; M. A. Ali; M. A. Anjum; N. Akhtar; S. Javed; M. A. Shakir (Journal of Animal and Plant Sciences, 2017)
Sole dependence on mineral fertilizers results high input cost for raising crops. Plant nutritionists are in search of substitutes to mineral fertilizers or the way that enhance the efficiency of mineral fertilizers or to compensate / supplement the mineral fertilizers. Rhizobium is very well recognized due to its symbiotic relationship with legumes has now been used in non-legumes due to its great root colonization ability, growth hormone production potential, improving the nutrient use efficiency, P-solubilization and inducing systemic resistance. Precursor-inoculum interaction provide constant source of hormones to plants and improved the growth and yield of cereals. Field studies were planned to ascertain the role of microbial biosynthesis of auxins through L-TRP on auxins production potential and wheat growth. Different Rhizobium species were isolated and screened out for their auxin production potential and root / shoot elongation assay was carried out. Two N levels i.e. 80 and 120 kg ha-1as urea was used while uniform rate of P (as SSP)and K (as SOP) i.e. 115 and 60 kg ha-1were used and L-TRP @ 10-5 M was applied as seed soaking for three hours. Results revealed that precursor-inoculum interaction has affected the yield parameters of wheat as compared to their separate application. Precursor-inoculum interaction produced highest grain yield of wheat at Soil Bacteriology Section, Soil Chemistry Section (Institute of Soil Chemistry & Environmental Sciences, ISC&ES) Faisalabad i.e. 5689, 5827 and 5042, 5292 kg ha-1 at 80 and 120 kg N ha-1, respectively. Other growth parameters, soil-plant analyses were also improved by the approach of precursor-inoculum interaction. Precursor-inoculum interaction exhibited higher IAA equivalents in the rhizosphere soil of wheat determined at 15 and 30 days after germination.
Keywords: L-TRP; Rhizobium; precursor-inoculum; IAA equivalents; wheat